Cardiovascular Imaging and Theranostics in Cardiovascular Pharmacotherapy - Mattia Cattaneo; Alberto Froio; Augusto Gallino (European Cardiology Review)
Imaging plays a pivotal role in the diagnostic and prognostic assessment of cardiovascular diseases. During the past two decades, there has been an expansion of the available imaging techniques, some of which are now part of routine clinical practice. Cardiovascular imaging of atherosclerosis is a useful instrument, and it can corroborate and expand pathophysiological evidence on cardiovascular disease, providing proof of concept for medical therapy and can predict its responsiveness, and it may be able to be used as surrogate endpoints for clinical trials. Theranostics is an emerging therapy that combines imaging and therapeutic functions, using imaging-based therapeutic delivery systems. Theranostics could partially overcome current imaging limitations and translate experimental evidence and large-scale trials assessing clinical endpoints, rationalising cardiovascular drug development and paving the way to personalised medicine. The medical community cannot overlook the use of cardiovascular imaging as a complementary and supportive adjunct to trials investigating clinical endpoints, which remain the mainstay for investigating the efficacy and safety of cardiovascular pharmacotherapy.